Depok City Informal Waste Facility Planning and Mapping using Geographic Information System (GIS) - Nursetyowati, Prismita; Muhammad Rahim Ranjany, Abdullah; Fairus, Sirin; Madonna, Sandra; Ayu Puspito Sari, Deffi (International Journal of Engineering and Technology, 2018)
Waste Bank, as the important pillar of waste management in Depok City have not been properly mapped. Based on these conditions, spatial analysis with Geographic Information System (GIS) helps to optimize the decision making process by the waste management stakeholder of Depok City related to informal waste facility. The stakeholder could also plan and assess the appropriate strategy for overall waste infrastructure in Depok City. The result shows that the active waste bank facility in Depok City (both the municipal solid waste bank and the unit waste bank) amounts to 82 waste banks of 428 registered waste banks. Most active garbage banks are in Tapos and Pancoran Mas sub-districts, while in Sawangan and Cinere sub-districts, there is no active waste bank exist. From the 67 interviewed waste bank managers in Depok City, 79% of waste bank units choose to deposit their waste to a municipal solid waste bank (Rumah Harum Waste Bank), and 12% to a bigger waste bank such as Depok Hijau Beji Waste Bank, the rest of waste bank units deposit their waste to collectors and one waste bank unit deposit the waste to Mr. Isnartoâ€™s Waste Bank at Merdeka Street. 20% of waste bank collects and weighs the waste at 9 AM while 14% of waste bank collects and weighs the waste at 8 AM. 11% of waste bank transport the waste at 12 PM. 67% waste bank operate in private locations and residence of the garbage bank managers. The maps produced in this research are distribution of Waste Banks, its cooperation, collection frequency, number of customer and operational location.Â